To compare corneal confocal microscopy of eyes with Fuchs' endothelial corneal dystrophy after two different endothelial surgeries. Issue 2 (March 2022) - Schiano-Lomoriello, Domenico; Abicca, Irene; Bono, Valeria; Giannini, Daniela; Colabelli-Gisoldi, Rossella Annamaria; Boni, Nicoletta; Komaiha, Chiara; Pocobelli, Augusto
Purpose: To study the features of corneal confocal microscopy of eyes with Fuchs' endothelial corneal dystrophy (FECD) after successful Descemet stripping automated endothelial keratoplasty (DSAEK) versus Descemet membrane endothelial keratoplasty (DMEK). Methods: Thirty-two eyes affected by FECD with corneal oedema requiring a corneal graft were treated with DSAEK (15 eyes) or DMEK (17 eyes). All patients underwent in vivo corneal confocal microscopy (IVCCM) at 6 months postoperatively. We evaluated preoperative and postoperative corrected distance visual acuity (CDVA) and the correlation with IVCCM characteristics. Results: Using IVCCM, Z-scan curve analysis showed similar subepithelial reflectivity peaks between the two groups (DSAEK 1256 SU ± 514 vs DMEK 1118 SU ± 408, p  = 0.411), while the interface reflectivity was significantly higher in the DMEK group (1511 SU ± 357) than in the DSAEK group (1029 SU ± 413, p  = 0.002). Conclusion: Comparing the corneal confocal microscopic characteristics after DMEK with those after DSAEK and their correlation with visual outcome at 6 months, we hypothesized that the presence of a third reflectivity peak in the Z-scan curves of DSAEK patients could justify the poorer visual outcome with this endothelial surgery than with DMEK.